THE CONTEXT OF TAUHID PRINCIPLES IN FAMILY EDUCATION IN THE ERA OF INDUSTRIAL REVOLUTION 4.O (SEMANTIC STUDY OF SURAH LUQMAN VERSE 13) - Ardi, Sahibul; Noor, Fatwiah; Nisa, Tahibatun; Anwar, M. (Proceeding of International Conference on Islamic Education (ICIED); Vol 7 No 1 (2022): Proceeding of International Conference on Islamic Education (ICIED), 2022)
Family education is a hot issue in the complex educational problems. It is considered as a crucial and fundamental education in equipping children for their future. In fact, the more educated people are the more-bad character they have. Luqman, in his story, had built a strong the foundation Tawhid at the beginning of the growth of his son. This is enshrined in the Koran as an ibrah and a prime role in educating children. The purpose of this paper is to study the context of the principle of Tawhid in family education in the era of the industrial revolution 4.O in Surah Luqman verse 13. This paper uses a qualitative approach with literature method. The data are collected through literature related to the theme, and the approach was carried out by semantic (meaning) and thematic analysis of the related verses. The study focuses on the principle of Tawhid from morphological and grammatical point of view ( الدلالة الصرفية والنحوية ). The result shows that the diversity of children's behavior is developed from the family. Therefore, the foundation of Tawhid becomes the main protect in facing the various changes and developments of the times.